Synthesis, structural and electrical characterization of a new organic inorganic bromide: [(C3H7)4N]2CoBr4. Issue 5 (20th January 2022) - Khalfa, M.; Oueslati, A.; Khirouni, K.; Gargouri, M.; Rousseau, A.; Lhoste, J.; Bardeau, J.-F.; Corbel, G.
Abstract : A new organic inorganic hybrid [TPA]2 CoBr4, where TPA = [(C3 H7 )4 N] + ( i.e., tetra-propyl-ammonium) compound has been synthesized by slow evaporation method at room temperature. Abstract : A new organic inorganic hybrid [TPA]2 CoBr4, where TPA = [(C3 H7 )4 N] + ( i.e., tetra-propyl-ammonium) compound has been synthesized by slow evaporation method at room temperature. Single crystal X-ray diffraction (SC-XRD), X-ray powder diffraction (XRPD), thermal analyses, vibrational and complex impedance spectroscopy have been used to characterize both structural, thermal, electrical properties. [TPA]2 CoBr4 crystallizes in the monoclinic system ( C 2/ c space group) with the following cell parameters: a = 33.145 (5) Å, b = 14.234 (3) Å, c = 15.081 (2) Å and β = 110.207 (5)°. In the crystal structure, the organic TPA cations which form layers stacked along the a -axis, are separated from each other by inorganic tetrahedral [CoBr4 ] 2− anions. The XRPD pattern confirms both the high purity of the sample and the crystalline nature of the powder. The differential scanning calorimetry (DSC) analysis shows an endothermic peak at 394 K upon heating which is ascribed to a structural phase transition since no decomposition of the titled compound is evidenced by thermogravimetric analysis. The ac conductivity and the dielectric properties confirm the presence of the phase transition. At the structural phase transition around 394 K, a change from a quantum mechanical tunneling to a correlated barrier hopping conduction models is determined from the temperature dependence of the exponent s of the Jonscher's power law. The analysis of complex impedance spectra shows that the electrical properties of the material are heavily dependent on frequency and temperature, indicating a relaxation phenomenon and semiconductor-type behavior. One single semicircle is detectable in the Nyquist plots of the complex impedance spectra which can be satisfactorily fitted with a combination R //CPE elements assigned to the bulk response. This behavior suggests that the sample is electrically homogeneous. Capacitance analysis proves the high effective permittivity at radio frequencies in the sample.